The Evolution of Colonial Legal Regulations in 19th Century Dutch East Indies Classical Literary Texts - fitriany, Aulia; Wahdatur Rike Uyunul Mukarromah; Wibowo, Satrio; Sudrajad, Wahyu; Handayani, Tuti (Universitas Kristen Cipta Wacana, 2024)
This study explores the representation of colonial law in 19th-century literary texts, examining how these works reflect and critique the colonial legal system. Using a qualitative approach with content analysis, the research focuses on how colonial law influenced various aspects of indigenous life, including social, cultural, and economic spheres. The study identifies key themes such as colonial law as a tool of oppression, resistance against colonial law, social stratification reinforced by colonial law, and law as a symbol of colonial power. Through literary works like